Modelamiento de un sistema de transmisión de potencia de dos etapas para detección de fallas a través del análisis de vibraciones (2020)
Actually, the design of mechanical systems is an important factor to their proper operation. Today, the components of most maquinary in the industry must satisfy some characteristics to have an useful life according to the time they are used. This machinary includes hydraulics pumps, gears, motors and others. Since preventive maintenance does not consider the real condition of the machine elements, it is necessary to implement predictive maintenance strategies that increase the e ciency of fault monitoring. Among these methods is the relationship of somes types of failures in rotating elements with an unusual vibration pattern, which can be detected through commercially available instruments. Therefore, a model was developed, that allows to adequately describe the behavior of these systems, to analyze this type of vibration. From this model, the vibratory behavior of a rotary system was analyzed, and the simulation of possible failures, which may happen at the time of an implementation in practice. Additionally, it was proposed a method for data acquisition such as accelerometer sensors, and the signals processing, in software specialized, can provide a useful solution to the industry.